Impact of The Russia-Ukraine Invasion on Wheat Imports in Indonesia Implications on Economic G rowth in Indonesia - Wali Akbar; Heru Subiyantoro (CV. Publikasi Indonesia, 2022)
This study uses secondary data by time series during period 2011 – 2021. The data was collected from various related sources such as literature books, journals and information from the internet. Sources of data that will be used in this study were obtained from relevant agencies, namely the Food and Agriculture Organization of the United Nations (FAO), the Indonesian Wheat Flour Producers Association (APTINDO), Bank Indonesia (BI), the Ministry of Trade of the Republic of Indonesia and the Central Statistics Agency. (BPS). Wheat consumption variable, rupiah exchange rate and wheat price simultaneously have a significant effect on foreign exchange reserves. With the impact of some of the variables above, Indonesia's wheat imports have increased so that full employment opportunities will be achieved and unemployment will decrease. The variable of wheat consumption partially has a significant and positive effect on imports of Indonesian. The exchange rate variable partially has a positive and significant and negative effect on Indonesian wheat imports. The international wheat price variable partially has a positive and significant effect on Indonesian wheat imports. Indonesian wheat import variable partially has a significant and positive effect on economic growth. The increase in Indonesian wheat imports indicates that economic growth will increase. Consumption of wheat flour, exchange rates and wheat prices have a significant effect on the volume of imports of wheat in Indonesia.